COMPARATIVE ANALYSIS PILE BEARING CAPACITY OF PILE FOUNDATIONS BASED ON SPT TEST RESULTS AND DYNAMIC TESTING DATA (Case Study: Construction of Halang Island Pier) - Siti Rahma Nadila; Gunawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The foundation is the lower structural part of a building that must be able to support the load of the structure above it. In foundation planning, the bearing capacity of the foundation can be calculated using soil investigation data and field load test data. This study aims to analyze and compare the bearing capacity of pile foundations using the empirical Mayerhof (1976) method based on N-SPT (Standard Penetration Test) data and the Hiley (1930) dynamic method based on driving record data from the Halang Island pier construction project in Rohil, Riau. The data used includes SPT test results from 3 drilling points (BH-01, BH-02, and BH-03) as well as driving record data from 40 pile driving points. The research subject consists of precast concrete piles with a diameter of 300 mm and an analysis depth of 42 m. The allowable bearing capacity (Qall) is calculated using a safety factor of 3. The analysis results show that the Mayerhof method yields a Qall value of 28.06 tons, while the Hiley method yields Qall values ranging from 15.30 to 29.93 tons. A comparison of the two methods reveals a ratio of 0.95 to 1.83 times, with a percentage difference ranging from -5.12% to 83.41%. The higher values in the Mayerhof method are influenced by the empirical correlation of N-SPT values representing soil conditions from investigations, whereas the Hiley method yields more conservative values because it accounts for the pile’s actual response during driving through energy transfer, penetration, and rebound. The research results indicate that the Mayerhof method is suitable for initial estimation of pile capacity, whereas the Hiley method is more representative in evaluating actual bearing capacity in the field.